Perspectives: Evaluation of Older Adult Cochlear Implant Candidates for Fall Risk in a Developing Country Setting - Rogers, Christine (Frontiers in Neurology, 2021)
Dizziness, vertigo, and falls are common in older adults. Data suggests that cochlear implant candidates are no different and could be argued to be at elevated risk due to the presence of hearing loss and likely vestibular involvement. Perspectives contextualises current testing paradigms and suggests a protocol suitable for use in developing country settings. Key words: Cochlear implants, developing countries, falls, older adults, vestibular deficits.